Extraction of ionosphere parameters in ionograms using deep learning - Mochalov Vladimir; Mochalova Anastasia (E3S Web of Conferences, 2019)
Based on a new developed author’s method for recognition traces of reflections from different layers of the ionosphere in ionograms, the ionosphere parameters are extracted. The method is based on the use of deep neural networks (DNN). The rules for extracting the ionosphere parameters in ionograms are given. Based on the results obtained by the authors, an intelligent support system for ionogram analysis is being developed.